Stomach content analysis of Osteochilus hasselti C.V from the Tarai River Tarai Bangun Village Tambang District Kampar Regency Riau Province - Nia Novita; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Osteochilus hasselti is found in the Tarai River that has been contaminated with organic pollution and it may affects the presence of food resources for the fish and as a consequence affects its stomach content. A study aims to understand the stomach content of O. hasselti has been conducted from November 2017 to January 2018. The fish was sampled 3 times, once/month.   There were 78 fishes captured. Stomach content were analyzed as a basis for calculating the Preponderence Index (IP). The analysis was conducted using a volumetric method. Results shown that the main food of the fish is Bacillariophyceae (IP 39.64%) and Chlorophyceae (IP 39.63%) . The small fishes (90-104 mm) consume phytoplankton, while the big fish (more than 130 mm) consume phytoplankton and zooplankton. The male and female’s stomach content was almost the same. Fish with relatively low maturity level eats mainly on phytoplankton, while mature fish consume phytoplankton and zooplankton.  Based on the data obtained, it can be concluded that the food of    O. hasselti was various, and it is related to body size and gonad maturity level. Osteochilus hasselti C.V adalah salah satu spesies ikan air tawar yang hidup di     Sungai Tarai. Sungai ini tercemar bahan organik dan mengalami penurunan kualitas air. Dampak yang ditimbulkan oleh pencemaran bahan organik adalah gangguan terhadap kehidupan biota di perairan tersebut, terutama menyebabkan isi lambung ikan bisa terganggu. Penelitian ini bertujuan untuk mengetahui isi lambung O. hasselti di sungai tersebut. Pengambilan sampel ikan dilakukan dari bulan November 2017 sampai Januari 2018. Pengambilan sampel dilakukan satu kali sebulan dalam waktu tiga bulan. Hasil tangkapan didapatkan 78 ikan. Penentuan indeks bagian terbesar makanan dengan  menggunakan metode IP (Indeks of Preponderance)dan analisis isi lambung menggunakan metode volumetrik. Hasil penelitian menunjukkan bahwa pada semua penangkapan ikan, isi lambung terdiri dari plankton. Makanan utama ikan paweh dari kelas Bacillariophyceae (40%). Berdasarkan hasil yang didapatkan, ikan ini dikatagorikan sebagai plankton feeder. Keywords: Fish feeding habit, Fish food habit, Plankton, Indeks of Preponderance